Використання ШІ-програм для створення презентацій у навчальному процесі - Олійник, В. М.; Бізюк, А. В. (ХНУРЕ, 2025)
Presentations are essential for conveying information in education, business, and research, yet creating high-quality presentations traditionally requires significant effort. AI tools simplify presentation creation by automating content, design, and visuals, aiding educators and students. However, they raise ethical concerns about originality, plagiarism risk, and content accuracy. This paper analyzes popular AI presentation tools, emphasizing their role as aids rather than replacements for independent work. It highlights the importance of critically evaluating AI-generated content to ensure reliable and ethically sound presentations.
Keywords: використання ШІ-програм; створення презентацій